THE EFFECT OF GIVING DATE JUICE ON INCREASING HAEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA AT KLUET UTARA HEALTH CENTER, SOUTH ACEH DISTRICT - T. Murhadi; Zuli Iklima Hayati (Jurnal Penelitian Progresif, 2023)
The prevalence of anemia in pregnancy in Indonesia increases every year due to various factors, the prevalence of anemia cases in 2018 was 48.9%. Data from the North Kluet Community Health Center for the period January to December 2021, the number of pregnant women was 632 people and 189 people experienced anemia (29.9%). From January to May 2022, the number of pregnant women was 324 people and 101 people experienced anemia (31.1%), consisting of 71 people with mild anemia, 20 people with moderate anemia and 10 people with severe anemia.